DAX Index Futures: Mispricing and Arbitrage in German Markets - Wolfgang Bühler; Alexander Kempf (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
The paper reports the results of an empirical study of the price relation between the German Performance Stock Index, DAX, and DAX futures. An ex-ante arbitrage strategy based on arbitrage signals is analyzed. The data set contains intraday bid- and ask futures quotes and index values on a minute by minute basis. It is found that the number and persistence of arbitrage opportunities differs considerably for futures nearest to deliver as compared to futures which are not nearest to deliver. The findings suggest that arbitrageurs trade mainly in futures nearest to deliver. The risk associated with arbitrage trading is found to be very small so that arbitrage profits are nearly risk free.
Keywords: 330